2016
DOI: 10.1037/aap0000058
|View full text |Cite
|
Sign up to set email alerts
|

Associations among perceived provider cultural sensitivity, trust in provider, and treatment adherence among predominantly low-income Asian American patients.

Abstract: Studies have consistently shown that Asian Americans’ rate of health-service utilization and treatment adherence is very low relative to other racial/ethnic groups. Asian Americans are also more likely than their European American counterparts to experience unfairness and discrimination in health care and to express lower trust in their health-care providers. This study examined the associations among Asian American patients’ perceived provider cultural sensitivity, trust in provider, and treatment adherence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The current authors found the importance of culturally sensitive communication and trust building in the client and HCP relationship should be built in stages, starting from the first visit and to be sustained over time. The current study findings are consistent with those of Kang et al’s (2016) survey study of perceptions in health care, who found that when Asian American clients’ level of perceived culturally sensitivity of a provider increased, their level of trust in providers and treatment adherence increased as well (Kang et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current authors found the importance of culturally sensitive communication and trust building in the client and HCP relationship should be built in stages, starting from the first visit and to be sustained over time. The current study findings are consistent with those of Kang et al’s (2016) survey study of perceptions in health care, who found that when Asian American clients’ level of perceived culturally sensitivity of a provider increased, their level of trust in providers and treatment adherence increased as well (Kang et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Little is known about what strategies are needed to strengthen health care practices within this population. One cross-sectional survey of Asian Americans’ perceptions of health care ( n = 63) found that cultural sensitivity of clinicians significantly predicted trust in HCPs and of treatment adherence (Kang, Tucker, Wippold, Marsiske, & Wegener, 2016). Although the results are not conclusive about the influence of client–provider gender concordance on CC screening completion in VAW, the information available suggests that this is important.…”
mentioning
confidence: 99%
“…Unlike self-reported questionnaires, which are often perceived by patients to be impersonal and lengthy, the two-way interactive discussion of PRISM+ could provide a means for engaging patients if disks selected are tailored to the individual [8, 67, 68]. Indeed, orientation of medical assessments towards the sociocultural context of illness is known to enhance trust in patients from CALD communities, satisfaction, and adherence to treatment [69, 70]. While satisfaction with the PRISM+ was not formally evaluated in this study, the PRISM face to face interaction was well received by participants, easily interpreted, and it has successfully been used to guide cultural adaptation of treatment [7].…”
Section: Discussionmentioning
confidence: 99%
“…55 These findings depart slightly from the existing body of research, however, which typically reports lower levels of trust and perceived lower quality of care among racial and ethnic minorities, compared with non-Hispanic white. 3,56 The setting for this study likely had a strong influence on reported findings. Specifically, the data were collected from community medical settings that are known for serving the Cambodian American community.…”
Section: Discussionmentioning
confidence: 99%
“…Asian Americans are the fastest growing racial/ethnic minority group in the US, and yet, remain largely understudied in health services research. [1][2][3] In addition to calling for more research on Asian Americans, in general, health scholars and advocates have identified the need for the disaggregation of data and analyses by Asian ethnic subgroups. [4][5][6][7][8][9] Asian Americans, with more than 20 ethnic subgroups, constitute a heterogeneous group comprised of diverse socioeconomic profiles, distinct languages, cultures, pre-immigration and post-immigration experiences, and health outcomes.…”
Section: Introductionmentioning
confidence: 99%